Synthesis of hydantoin and thiohydantoin related compounds from benzil and study of their cytotoxicity - A. Kashem Liton and M. Rabiul Islam (Bangladesh Pharmacological Society, 2006)
Condensation of benzil (1) with urea, monophenyl urea and diphenyl urea in the presence of absolute ethanol using 30% aqueous NaOH gave the products 1a, 1b and 1c respectively and also with thiourea, monomethyl thiourea, dimethyl thiourea and diethyl thiourea the products 2a, 2b, 2c and 2d were obtained. Methylation of the product, 2a in the presence of dimethyl formamide (DMF) using K2CO3 formed 2. The compounds 1b, 1c, 2b, 2c and 2 showed highly cytotoxic activity and the compounds 1a, 2a, 2d showed relatively low cytotoxic activity against brine shrimp lethality bioassay.